Knowledge and the Indian Ocean : Intangible Networks of Western India and Beyond - Keller, Sara. (Cham : Imprint: Palgrave Macmillan, Imprint: Palgrave Macmillan, 2019)
This volume examines Western India's contributions to the spread of ideas, beliefs and other intangible ties across the Indian Ocean world. The region, particularly Gujarat and Bombay, is well-established in the Indian imaginary and in scholarship as a mercantile hub. These essays move beyond this identity to examine the region as a dynamic place of learning and a host of knowledge, tracing the flow of knowledge, aesthetic sensibilities, values, memories and genetic programs. Contributors traverse the fields of history, anthropology, agriculture, botany, medicine, sociology and more to offer path-breaking perspectives on Western India's deep socio-cultural impact across the centuries. Western India emerges as a pivotal region in the maritime world as a transmitter of knowledge.
1. Introduction -- I. Knowledge, Science and Techniques -- 2. Places We Can Go: Some notes on sea/knowledge -- 3. Knowing the Sea: Thalassographies to Thalassology of the Indian Ocean (up to c. 1500 CE) -- 4. A Chinese Muse in the Caliph's Court - The Influence of Chinese Ceramic Technology across the Indian Ocean (8th to 14th Century CE) -- 5. Ava: A Living Tradition of Reverence for Water among the Zoroastrians -- 6. Scholars in Gujarat's Bazaars-Revisiting L'académie ambulante ("The Roving Academy") -- 7. Gujarat Ornamental Furniture: Artisans, Techniques, Skills and Global Markets during the Nineteenth Century -- 8. 'Without a Counterpart on the Globe": Geographical Knowledge and the Mapping of "Kutch" in the Nineteenth Century -- II. Skill, Migration and Identities -- 9. Gujarat Sufis, "Sants" and the Indian Ocean World in Medieval Times -- 10. Doing Well but also Doing Good? East African Indian Merchants and Their Charitable Work, c. 1850-1920 -- 11. Narratives of Transcendental Decision-Making: Seeking Health and Healing at Sufi Shrines in Gujarat -- 12. Voices of the Sidis: The Tradition of the Fakirs -- 13. Linguistic and Cultural Contributions of Gujarat in Eastern Africa -- 14. The Transnational Life and Political Philosophy of Shyamji Krishnavarma.
Description based on publisher-supplied MARC data.
Keywords: Africa-History.; Asia-History.; Civilization-History.; Social history; World history; World History, Global and Transnational History; African History; Asian History; Cultural History; Social History